Surgical management of giant pulmonary artery aneurysms in patients with severe pulmonary arterial hypertension. Issue 4 (18th January 2022) - Doi, Atsuo; Gajera, Jay; Niewodowski, Daniel; Gangahanumaiah, Shivanand; Whitford, Helen; Snell, Greg; Kaye, David; Joseph, Tim; McGiffin, David
Abstract: Background and Aim: Giant aneurysm of the pulmonary artery (PAA) is an extremely rare condition that may develop in patients with pulmonary arterial hypertension (PAH) which may be complicated by rupture, dissection or intravascular thrombus formation. The aim of this study was to examine available literature with regard to surgical strategies in patients undergoing transplantation for PAH with PAA. Results: These patients were traditionally considered for heart–lung transplantation but more recently, there have been reports of successful lung transplantation with reconstruction of the pulmonary artery. Conclusions: Unless there is a mandatory indication for heart–lung transplantation, patients with PAH and PAA can undergo lung transplantation and reconstruction of the pulmonary artery without compromising the outcome.